"Men, money, and motors": The motor car as an emerging technology in Australian Federal Election Campaigns, 1903–31. Issue 2 (August 2019) - Monnox, Chris
The appearance of the car in early twentieth-century Australia significantly re-shaped election campaigns. Political parties used cars to bring voters to polling places, and some voters took advantage of elections by making their voting contingent on these free rides. Politicians and other campaigners took exception to the cost of supplying cars and to the attitudes evident in demands for rides. Some saw compulsory voting as a way of forcing voters to provide for their own transportation. Introduced mostly in the 1920s, compulsory voting's impact was initially muted. But over time it did change how cars were used in Australian politics. One hundred years on compulsory voting remains in force in Australia, and cars are still seldom used on election day. This serves as an enduring example of how new technologies could have a disruptive impact on campaigning prior to the advent of radio and television.